Hagiographical Narrative and Apocryphal Imagination in the Syriac Story of Pawla the Priest - Minov, Sergey (Scrinium, 2023)
Taking the newly discovered Syriac composition, entitled Story of Pawla the priest, as an example, the article explores some literary aspects of Christian hagiographical writing in the late antique Syria-Palestine in its relation to the New Testament apocryphal literature. It focuses on the author’s representation of the bathhouse as a heterotopic and liminal space, and his construction of the imaginary community of Herodians, and discusses the shifting and porous divide between apocryphal and hagiographical avenues of cultural memory during Late Antiquity. In Appendix, an English translation of the relevant parts of the Story is offered.